Key Issues of International Legal Regulation of Autonomous Maritime Navigation - V. V. Gavrilov; R. I. Dremliuga (Московский журнал международного права, 2020)
INTRODUCTION. On the basis of provisions of the 1982 UN Convention on the Law of the Sea and other legal documents, the article analyzes topical issues of the current and future international legal regulation of the use of maritime autonomous surface ships (MASS), which are capable of completely transforming the shipping and international maritime transportation industry in the near future.MATERIALS AND METHODS. The issues raised in the article are structurally divided into three maingroups. The first one is connected with the anthropocentrism of the ‘pre-digital era’ law – that is, with its inability to work with other autonomous subjects except for people and various forms of their organization. The second is determined by specific characteristics of autonomous systems themselves, among which their non-determinism and ability to self-study should be noted. The third group is directly related to the legal support of MASS cybersecurity in the new conditions.RESEARCH RESULTS. When writing the article, the authors proceeded from the fact that the issue of extending the application of international maritime law to MASS cannot be solved by simply transferring its regulatory impact to new subjects (objects) – artificial intelligence systems or autonomous ships themselves. Such a transfer is impossible, since human and artificial intelligence use completely different decisionmaking algorithms.DISCUSSION AND CONCLUSIONS. Th  main conclusion of the article is that the widespread integration of MASS into the practice of international maritime transportation will be a turning point not only for the very procedure for its performance, but also for the algorithm of legal regulation of this sphere of public relations. Since the emergence of autonomous ships will mainly result in a gradual decrease of the human component in managing them in favor of artificial intelligence and related automated systems, international law of the sea is unlikely to continue to operate in its current form. It will take a lot of work to adapt and change its norms in accordance with the new realities of the ‘digital era’ of human development.